The use of a customized mounting guide for Implant-Prosthetic Restoration of the Fully Edentulous Arch - Gregor-Georg Zafiropoulos; Evangelos Sotiropoulos; Tae Ho Yoon; Moosa Abuzayda (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Reconstruction of fully edentulous arches with implant-retained dentures requires thorough planning and precise registration of the interocclusal relationship, to achieve a successful treatment outcome. This technical report describes three representative approaches from a cohort of 89 fully edentulous arches in 69 patients who were treated with the described mounting guide technique. A technique of using a duplicated denture as a guide is described, which allows for the accurate transfer of the occlusal relationship and vertical dimensions, while facilitating the full-arch restoration process with implantretained fixed or removable dentures and reducing the number of required in-office sessions.